1073 Synchronous Cholecystitis and Appendicitis: A Case Report Highlighting Learning Points on Medical Imaging and Consent. (12th October 2021) - David, B; Issa, M; Gallucci, A
Abstract: Laparoscopic appendicectomy and laparoscopic cholecystectomy are separately two of the most common emergency surgical procedures carried out in the UK. Only a small number of synchronous presentations of acute appendicitis and acute cholecystitis have been reported in surgical literature and this rare co-existent pathology gives rise to several valuable learning points with regards to laparoscopy, medical imaging interpretation and the consent process. Our case report involves a 58-year-old female patient presenting with both RUQ and RIF pain and positive Murphy's sign on clinical examination. US scan demonstrated several gallstones within a thin-walled gallbladder. Subsequent CT scan reported acute appendicitis which was treated definitively with laparoscopic surgery. Intraoperatively a perforated gangrenous gallbladder containing multiple calculi was discovered, and the decision was made to perform a double procedure of laparoscopic appendicectomy and cholecystectomy. Histopathology confirmed synchronous pathology of appendicitis with faecolith and calculus cholecystitis. This case demonstrates the importance of considering multiple pathologies when assessing a patient with ambiguous and migratory abdominal pain. It reinforces the importance of diagnostic laparoscopy to rule out multiple pathologies. This acts as a cautionary case against over-reliance on medical imaging and reminds surgeons of their obligation to maintain competence in CT interpretation plus correlation of imaging with clinical assessment of the patient. Readers should also be reminded that the consent process for surgical interventions should be undertaken meticulously in patients with ambiguous abdominal pain.